2022
DOI: 10.1515/tjb-2021-0201
|View full text |Cite
|
Sign up to set email alerts
|

Early creatinine and e-GFR changes as prognostic predictors of COVID-19 patients

Abstract: Objectives We aimed to investigate the effects of the COVID-19 disease on kidney functions and early prognosis. Materials and Methods All cases were divided into those discharged and exitus cases. The patients were diagnosed with acute kidney injury (AKI) according to the KDIGO criteria. Results As a result of the ROC analysis, the patients with a creatinine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This finding was consistent with previous reports of higher plasma glucose and creatinine levels in critically ill COVID-19 patients. ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with previous reports of higher plasma glucose and creatinine levels in critically ill COVID-19 patients. ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed significant elevations of phenotypes related to kidney function for the severe endotype, with average levels of both creatinine and BUN in the abnormal range, suggesting an initial tendency toward kidney dysfunction among these individuals. 45 , 46 Vitamin D is known to play a critical role in immunomodulation; sufficient levels are therefore particularly important for IDs like COVID-19 and influenza. 47 , 48 Consistent with this finding, we identified that average levels of vitamin D were insufficient among the severe endotype resulting in further susceptibility.…”
Section: Discussionmentioning
confidence: 99%